WAIS Divide sulfate and nitrate isotopes - Alexander, Becky; Steig, Eric J. (IEDA: US Antarctic Program Data Center, 2017)
This data set contain oxygen isotopes of sulfate and nitrate and nitrogen isotopes of nitrate from the WAIS Divide ice core from the surface to 577 m depth at varying resolution